The Phenomenon of Match-Fixing in Soccer: A Plague Without a Cure? - Petropoulos, Nikolaos (2018)
Introduction: Today, match-fixing is considered as one of the most significant threats to the integrity of soccer. Everyone seems to talk about it. However, the phenomenon itself has received relatively limited academic interest despite the media coverage that match-fixing scandals have enjoyed, mainly over the last 10-15 years. This study will seek to explore the match-fixing landscape and provide a detailed account of how extensive the phenomenon is and who are the main stakeholders.To achieve this goal, we will rely heavily on a series of INTERPOL bi-weekly reports on match-fixing cases that cover the period from 1st of January 2013 until 30th of June 2017. Methods: The present dissertation will utilize the tools of secondary data analysis and quantification of qualitative data to pursue its objectives and test a series of hypotheses. The process of conducting a quantitative analysis of qualitative data will include three main steps: First, organize the data; second, read it and code it and third, and then present and interpret it. To conduct the analyses, the main statistical tools used include descriptive statistics, correlations, T-Test and Analysis Of Variance (ANOVA). SPSS statistical software was used to conduct the data analysis. Theoretical framework: To better understand the phenomenon of match-fixing the present study utilized and drew from three major criminological theories, namely Differential Association, Routine Activity, and Strain theory. Discussion and findings: Match-fixing is a significantly widespread phenomenon that could occur at –literally- every country on the planet. While various stakeholders are involved in match-fixing cases, the analyses conducted in the present study show that players are heavily involved in fixed games and are the most likely to get arrested in countries that legislation is in place. Additionally, organized crime syndicates play an important role and are involved in match-fixing cases across the globe. More importantly, it seems that corruption is a key in addressing match-fixing as countries who rank low in the corruption index are not only less willing to introduce effective anti- match-fixing criminal legislation but are also ineffective in curtailing the phenomenon. Also, although the criminal law is an important tool against match-fixing our findings demonstrate that specialized legislation that appears to be more effective and promising than ordinary criminal law measures.However, it is not just the criminalization of match-fixing that is important; both criminalization of the phenomenon and penalty severity could prove promising regarding unveiling players’ participation in match-fixing, according to our findings Conclusion: A series of recommendations were made based on the finding of this study. The analyses show that countries across the globe with a focus on the most corrupted one should implement and effectively use specialized legislation on match-fixing to curtail the phenomenon. Unless said legislation is introduced, the majority of match-fixing plots will remain below the radar maintaining a deceiving sense of immunity from the phenomenon. Also, more attention should be paid to the role of players in match-fixing as our statistical findings suggest that their involvement in match-fixing cases is not only significant but quite extensive as well